New potential application of hydroxypropyl-β-cyclodextrin in solid self-nanoemulsifying drug delivery system and solid dispersion. (1st November 2021) - Kim, Jung Suk; Choi, Yoo Jin; Woo, Mi Ran; Cheon, Seunghyun; Ji, Sang Hun; Im, Daseul; ud Din, Fakhar; Kim, Jong Oh.; Youn, Yu Seok; Oh, Kyung Taek; Lim, Soo-Jeong; Jin, Sung Giu; et al.
Abstract: The purpose of this study was to use hydroxypropyl-β-cyclodextrin (HP-β-CD) as a novel carrier in solid SNEDDS and solid dispersions to enhance the solubility and oral bioavailability of poorly water-soluble dexibuprofen. The novel dexibuprofen-loaded solid SNEDDS was composed of dexibuprofen, corn oil, polysorbate 80, Cremophor® EL, and HP-β-CD at a weight ratio of 45/35/50/15/100. This solid SNEDDS spontaneously formed a nano-emulsion with a size of approximately 120 nm. Unlike the conventional solid SNEDDS prepared with colloidal silica as a carrier, this dexibuprofen-loaded solid SNEDDS exhibited a spherical structure. Similar to the dexibuprofen-loaded solid dispersion prepared with HP-β-CD, the transformation of the crystalline drug to an amorphous state with no molecular interactions were observed in the solid SNEDDS. Compared to the solid dispersion and dexibuprofen powder, solid SNEDDS significantly enhanced drug solubility and AUC. Therefore, HP-β-CD is a novel potential carrier in SNEDDS for improving the oral bioavailability of dexibuprofen. Highlights: Hydroxypropyl-β-cyclodextrin (HP-β-CD) was used as a novel carrier in solid SNEDDS and solid dispersions. Solid SNEDDS was fabricated with corn oil, polysorbate 80, Cremophor® EL, and HP-β-CD. Solid dispersion was prepared with HP-β-CD and polysorbate 80. Solid SNEDDS considerably improved the bioavailability of dexibuprofen.